The Contribution of Interfaith Dialogue toward a Culture of Peace (American Journal of Islam and Society, 2002)
Dialogue among the adherents of the major world religions has alwaystaken place, especially, but not only, among the Abrahamic faiths: Judaism,Christianity and Islam. Excellent examples of this may be found in themidst of shared histories where we are more often presented with a recordof conflicts. The high points must be the enormously rich and creative interactionswhich took place in medieval Islamic Spain and southern Italy andat various times in places as far apart as Central Asia, Baghdad, Delhi,Cairo and the Ottoman Empire.As a movement with its institutions and full-time professionals, andnetworks of activists, interreligious dialogue is primarily a phenomenonof the twentieth century. It is the pressures of this century which havedemanded that we mobilize the resources of the great religions for dialogueand peace, purposes which have historically often seemed marginal.In India, the realization that a reasonably unified independence wouldonly be achieved if religions could work together, actually provides asignificant impetus towards the cooperation of religious leaders andinstitutions.The horrors of Nazi genocide in Europe spurred post-war generationstowards a radical review of traditional Christian attitudes towards Judaism.Out of regional tragedies, like the wars in Lebanon and in the formerYugoslavia, have come strengthened efforts across the social spectrum todisarm religious hatreds. The resurgence, in the last couple of decades, ofpolitical radicalism motivated by religion and expressed in religious terms, ...